Podkrzywdzie – świat mitu, tajemnicy i Schulza Propozycja lektury intertekstualnej - Bagłajewski, Arkadiusz (Śląskie Studia Polonistyczne, 2016)
The presented interpretation of Andrzej Muszyński’s Podkrzywdzie constitutes an attempt at situating the work in the perspective of its references to some determinants of Bruno Schulz’s poet ics and his literary worldview, especially to the concept of mythologization of the represented world and the linguistic practices, referring to the consistent stylization which has its roots in the fiction of the author of The Cinnamon Shops. The proposed intertextual reading leads to the conclusion about the creative restitution of Schulz’s model, while at the same time enabling one to inscribe Muszyński’s novel debut, mythographic creation of Podkrzywdzie in the literary trend of “small homelands,” unex pectedly reviving in the second decade of the 21st century.